PROGRAM KESEHATAN, KESELAMATAN KERJA (K3), DISIPLIN KERJA, DAN INSENTIF KERJA PENGARUHNYA TERHADAP PRODUKTIVITAS KERJA KARYAWAN - Iman Adisatya Wibowo (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2021)
The purpose of this study was to determine the effect of health programs, work safety, work discipline, and work incentives on the productivity of employees of the PT. Sandabi inda sustainable. And to find out which factors are the most dominant in influencing employee productivity.This research is a quantitative research. The sampling technique in this research is saturated sampling as many as 126 employees of the factory division of PT. Sandabi Indah Lestari.Based on the results of data analysis, the results show that: 1) Partially the variables of Health, Safety (K3), Work Discipline, and Work Incentives, on employee productivity at PT. Sandabi Indah Lestari. As evidenced by tcount> ttable (2.241> 1.657) and tsig <α = (0.027 <0.050), tcount> t table (5.321> 1.657) and tsig <α = (0.000 <0.050), tcount> t table (3.666> 1.657) and tsig <α = (0.000 < 0.050). 2). Simultaneously the variables of Health, Work Safety (K3), Work Discipline, and Work Incentives have an effect on employee productivity at PT. Sandabi Indah Lestari. As evidenced by the Fcount of 35,879 with a Ftable value of 2.68, namely (35,879> 2.68) and tsig <α = (0,000 < 0.050) which means that Health, Work Safety (K3) (X1), Work Discipline (X2) and Work Environment ( X3) together have a significant effect on employee productivity at PT. Sandabi Indah Lestari.Keywords: K3, Discipline, Incentives, and Productivity.